Double-stranded RNA antibodies in systemic lupus erythematosus. Issue 3 (June 1975) - Davis, P; Cunnington, P; Hughes, G R
Abstract : Antibodies to viral double-stranded RNA (ds RNA) have been found in 40% of patients with systemic lupus erythematosus (SLE) and 14-5% of patients with rheumatoid arthritis. These antibodies were diagnostically more specific SLE than those directed against artificial polynucleotides, poly I:C and poly A:U. Although not disease specific, high titres of antibody to ds viral RNA were found almost exclusively in SLE. Serial studies failed to show that RNA antibody levels correlated with disease activity. Although of considerable interest in experimental studies on the pathogenesis of SLE, ds viral RNA antibodies are of little clinical significance in the management of SLE.